Comparison of Beta-Glucuronidase Expression and Anatomical Localization in Bombarded Immature Embryos of Banana Cultivar Mas via Biolistic Transformation - Chee, W.W.; Jalil, M.; Abdullah, M.O.; Othman, R.Y.; Khalid, Norzulaani (Malaysian Society for Molecular Biology and Biotechnology, 2005)
To obtain stable expression of a foreign gene, it is important to have optimized conditions for plant genetic transformation. Here, a GUS intron-containing gene driven by CaMV 35S promoter was used to optimize the conditions of biolistic transformation of banana immature embryos and also for the study of GUS localization in the transformed cells. The GUS activity detected histochemically and fluorometrically were further analysed by microscopy. This histological study confirmed the results in the histochemical and fluorometric assay, where highest expression of GUS was achieved when the immature embryos bombarded with the helium pressure of 1350 psi and placed at the target distance of 6 cm. The observation of strong GUS staining in the deep layers of the cell structure were produced by higher acceleration pressure and shorter target distance, whereas weak GUS staining in the plant epidermis layer were observed in most lower acceleration pressure and higher target distance. The study of GUS localization on biolistic transformation provided more reliable parameters for transformation. It may also indicate the locality of the foreign gene expression area in the transgenic plant that can provide more understanding of the nature of transgene and its integration.